Student’s View on Online Education during the COVID-19 Pandemic - Basnet, Saraswati; Basnet, HomBahadur; Bhattarai, DilipKumar (Rupantaran: A Multidisciplinary Journal, 2022)
During COVID-19 pandemic, in many part of the world were closed educational Institution so impacting around 286 million student which is (48 per cent girls) preprimary to higher education level too. Online education is electronically supported learning that relies on the internet for teacher/student interaction and the distribution of class materials The aim of the Narrative -analysis is to evaluate the student’s view on online education during the COVID-19 pandemic by performing a systematic narrative analysis of related published literature. The Narrative analysis was done diverse subjects and diverse research design was eligible among the 21 full-text articles. A formal extraction protocol was the PRISMA-P. Majority of the student’s feels that physical class was more effective than online class in terms of accessibility, easy to use resources, and importance to enhance teaching-learning habit. Most of the students (91.7%) felt that online classes should be continued during pandemic but only nearly two third of the respondents (63.2%) were satisfied with the online classes. They experience in transitioning to online education include poor network, lack of digital skills, lack of technological support from institutions among others. Study identified student’s views on online education are variation among context to context.